PENGARUH PEMBERIAN BUKU SAKU GOUTY ARTHRITIS TERHADAP PENGETAHUAN, SIKAP DAN PERILAKU PASIEN GOUTY ARTHRITIS RAWAT JALAN DI RSUP. PROF. DR. R. D. KANDOU MANADO - Irza Nanda Ranti (POLTEKKES KEMENKES MANADO, 2012)
Gouty Arthritis Prevalence patients Installation outpatient clinic Outpatient department ofInternal Medicine Rheumatology section. Prof. Dr. R. D. Kandou Manado, is quite highand it is not matched with the patient's knowledge. This is due to the lack of correctinformation will diet and eating patterns. Thus the researchers created a booklet anddistributed free gouty arthritis.The purpose of this study to determine the effect of gouty arthritis counseling handbookon knowledge attitude and behavior of the patient and the control of purine intake andblood uric acid levels of patients Gouty Arthritis Installation outpatient clinic Outpatientdepartment of Internal Medicine Rheumatology section. Prof. Dr. R. D. Kandou Manado.Methods This study is a quasi-experimental study (quasi-experimental) design with preend post-test control group design. Subjects were patients Gouty Arthritis Installationoutpatient clinic Outpatient department of Internal Medicine Rheumatology section. Prof.Dr. R. D. Kandou Manado. Research using the two treatment groups. That interventiongroups using a paperback book gouty arthritis and the control group was not givenpocket book gouty arthritis.With the effects of gouty arthritis booklet on knowledge, attitudes and behavior of thepatient during the intervention showed improvement. Knowledge of patients increased by1.16%, while the attitude increased by 5.50%, and increased by 5.60% behavior. As forthe control group (not supplied booklet gouty arthritis) during the study did not showsignificant improvement, patient knowledge there is no increase or decrease is 0.00%,while the same attitude that is 0.00%, and the behavior is not significantly increased asmuch as 0.60%.The conclusion is gouty arthritis booklet can improve knowledge, attitude and behavior ofpatients Gouty Arthritis Installation outpatient clinic Outpatient department of InternalMedicine Rheumatology section. Prof. Dr. R. D. Kandou Manado.